Kemampuan Menulis Arab Melayu Mahasiswa Non Muslim Angkatan 2021 PBSI Universitas Riau - Indah Rahayu Putri; Sonia Sony; Lenny Lestari; Hasnah Faizah; Hasnah Faizah AR (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Research in Malay Arabic writing for non-Muslim students is a study to test the ability of non-Muslim students in Indonesian language and literature education and aims to examine in detail the ability to write Malay Arabic words and apply the rules for writing correct words in Malay Arabic writing. The method in this research is descriptive quantitative, which is a method of describing using numbers and diagrams by explaining the percentage of numbers and diagrams with data that has been obtained from research samples taken in a recorded manner and using samples. Examining and analyzing the data that has been obtained using qualitative descriptive techniques concludes that the ability to write Malay Arabic writing for non-Muslim students of the Indonesian Language and Literature Education Study Program. This research is also useful for finding writing errors for non-Muslim students and evaluating our mistakes as teachers. The results of the study concluded that the writing ability of non-Muslim students was 20.